Apparent digestibility of a traditional and a pelleted ration for horses - Manzano, Airton; Carvalho, Roberto Thomaz Losito de (Pesquisa Agropecuaria Brasileira, 2014)
This experiment was carried out in order to compare pelleted ration (RCP) versus traditional feeding (AT) on the digestibility of nutrients. It was used fourteen growing females, twelve Arabian and two high grade (15/16) Arabian cross, with average age of 32 months and average weight of 274 kg. The two treatments ware compared by a paired design, the animals divided in seven pairs according to weight and age. There was no significative differences between the treatments with respect to the digestibility of dry matter and other nutrients. It was concluded that form of the treatments did not affect the digestibility coefficients.